Medial Turn in Education: Philosophy of Understanding Words and Images - Grigoryev, Sergey L.; Saenko, Natalya R.; Volkova, Polina S.; Kortunov, Vadim V. (Frontiers in Education, 2022)
The research presented in the article aimed to diagnose the profound changes that have taken place in the education as a result of expansion of screen technologies and introduction of distance interaction in pedagogy. The live sounding speech of a teacher is the true historical form of paideia as such and the technique of maieutics in particular. Any intermediary, even a writing process, let alone the screen, reduces the effect of pedagogical dialogue and produces significant and radical changes in understanding of meaning. The article deals with the problems of understanding in the pressing context of two turns of educational philosophy: linguistic and medial. The empirical background of these turns is represented, on the one hand, by the increasing extent of the visualised (“printed”, “screened”) word in educational procedures versus the sounding word, and by the irreversible introduction of screen technologies, digitalisation and distance learning, on the other hand. The consideration is made through the prism of comprehension-based approach focusing on the values and meanings of professional pedagogical activity; the systemic approach, the principles of language sign ambivalence, the method of stylistic decoding, the method of analysis of vocabulary definitions and intertextuality.